Warfield on Inspiration and Inerrancy - Thompson, Mark D. 1959- (2021)
Objections have been raised to Warfield's doctrine of inerrancy, relating to logical incoherence, a misuse or blindness to evidence, and the creation of an ideal which, rather than strengthening confidence in the Scriptures we have in our hands today, has itself contributed to disillusionment and even the abandonment of faith by some. These are serious charges, but far too often, they are made with only a superficial knowledge of what Warfield actually said and wrote. This article seeks to make an assessment of his contribution with a greater degree of fairness and with deeper appreciation.